2017
DOI: 10.1037/neu0000337
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive outcomes in early-treated adults with phenylketonuria (PKU): A comprehensive picture across domains.

Abstract: Objective: Phenylketonuria (PKU) is an inherited metabolic disease which affects cognitive functions due to an inability to metabolize phenylalanine which leads to the accumulation of toxic by-products (Phe) in the brain. PKU can be effectively treated with a low phenylalanine diet, but some cognitive deficits remain. Studies have reported impairments, especially for processing speed and executive functions, but there is a lack of comprehensive assessment across cognitive domains. Moreover, it is important to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
103
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 57 publications
16
103
1
Order By: Relevance
“…A number of well‐controlled studies reported statistically significant deficits in patients compared with healthy control groups or normative populations across a range of neuropsychological and executive functions, including sustained and selective attention, working memory, response inhibition, and letter fluency . Two studies that performed extensive analyses on the same cohort of patients reported impairments in patients with ETPKU vs healthy controls, in the higher order executive functions, visuo‐spatial attention and visuo‐motor coordination, with significant variability across patients . Additionally, a recent study reported that compared with a control group, patients with ETPKU showed deficits in complex language tasks and were slower and less accurate in tasks requiring planning and strategic abilities .…”
Section: Iq and Neuropsychological Outcomesmentioning
confidence: 99%
“…A number of well‐controlled studies reported statistically significant deficits in patients compared with healthy control groups or normative populations across a range of neuropsychological and executive functions, including sustained and selective attention, working memory, response inhibition, and letter fluency . Two studies that performed extensive analyses on the same cohort of patients reported impairments in patients with ETPKU vs healthy controls, in the higher order executive functions, visuo‐spatial attention and visuo‐motor coordination, with significant variability across patients . Additionally, a recent study reported that compared with a control group, patients with ETPKU showed deficits in complex language tasks and were slower and less accurate in tasks requiring planning and strategic abilities .…”
Section: Iq and Neuropsychological Outcomesmentioning
confidence: 99%
“…Studies have shown that EFs are commonly affected across metabolic diseases. In this issue, Crowe et al have Palermo et al, 2017). Finally, Bergeron et al have reported impairments in Niemann-Pick C, again, in the Trail Making B and in span tasks involving monitoring.…”
Section: Advancing Our Understanding Of the Architecture Of Cognitionmentioning
confidence: 91%
“…In addition, not only language but also memory and learning (including spelling, which requires memorization of irregular words in English) appear relatively preserved. These functions may be sub-optimal in individuals with poor dietary control, but they do not show the significant group impairment shown in tasks requiring visual attention and executive functions (EFs; see Palermo et al, 2017;Romani et al, 2017). A similar pattern-with more severe impairments in visual attention than in language tasks (particularly lexical-retrieval tasks)-is seen in ageing, which is also characterized by a degradation of the myelin sheet, important for the speed of axonal transmission (e.g., see Jenkins, Myerson, Joerding, & Hale, 2000).…”
Section: Advancing Our Understanding Of Cognition and Neuron Metabolismmentioning
confidence: 99%
“…Despite treatment, subtle cognitive deficits are still observed in ETAwPKU. [28][29][30] Underlying mechanisms are still under debate, and there is wide inter-individual variability, but such deficits have been associated with observed disruptions in brain pathophysiology (eg, demyelination and disturbed neurotransmitter synthesis). Some observed disruptions are similar to those seen in healthy ageing, but occur at a younger age in ETAwPKU (see Box 2).…”
Section: Brain Healthmentioning
confidence: 99%